2017
DOI: 10.1038/s41598-017-02095-3
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor IRF6 Co-Represses PPARγ-Mediated Cytoprotection in Ischemic Cerebrovascular Endothelial Cells

Abstract: Activation of peroxisome proliferator-activated receptor gamma (PPARγ) in the cerebrovascular endothelium is a key suppressor of post-stroke brain damage. However, the role of PPARγ’s co-regulators during cerebral ischemia remains largely unknown. Here, we show that the transcription factor IRF6 is a novel PPARγ co-regulator that directly binds to and suppresses PPARγ activity in murine cerebrovascular endothelial cells. Moreover, IRF6 was also revealed to be a transcriptional target of PPARγ suppression, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Interestingly, amongst all microRNAs, both miR-424 and miR-503 are predominantly regulated by estrogen [ 60 , 61 ] while miR-503 is known to control female CD4 + T cell activation and as such the acute inflammatory response in women [ 62 ]. More support for elevated X-linked miR expression and potential sex-specific downstream effects in brain ECs was demonstrated in OGD cultured cerebral ECs which increased miR-106a expression, thereby decreasing cell viability, leading to cell death due to an increased and pro-inflammatory caspase-3 expression [ 63 ]. Also, murine cerebrovascular endothelial cells displayed less cell viability upon transient MCA occlusion in C57BL/6 J male mice ( n = 24, 8–10 weeks old), a phenotype induced by elevated miR-106a expression [ 63 ].…”
Section: Stroke Promoting Mechanismsmentioning
confidence: 99%
“…Interestingly, amongst all microRNAs, both miR-424 and miR-503 are predominantly regulated by estrogen [ 60 , 61 ] while miR-503 is known to control female CD4 + T cell activation and as such the acute inflammatory response in women [ 62 ]. More support for elevated X-linked miR expression and potential sex-specific downstream effects in brain ECs was demonstrated in OGD cultured cerebral ECs which increased miR-106a expression, thereby decreasing cell viability, leading to cell death due to an increased and pro-inflammatory caspase-3 expression [ 63 ]. Also, murine cerebrovascular endothelial cells displayed less cell viability upon transient MCA occlusion in C57BL/6 J male mice ( n = 24, 8–10 weeks old), a phenotype induced by elevated miR-106a expression [ 63 ].…”
Section: Stroke Promoting Mechanismsmentioning
confidence: 99%
“…Two previous reports also showed that IRF6 regulates Pparγ gene in macrophages and endothelial cells. (31,32) These studies, combined with our findings, suggest a more generalized transcriptional target gene for IRF6; however, we investigated a unique function of IRF6 in regulating different disease from the current report with different molecular mechanism. Moreover, each IRF member may have a wide spectrum of direct target genes depending on the disease setting.…”
Section: Discussionmentioning
confidence: 68%
“…Our data show that IRF6 directly binds to the promoter of the PPARγ gene and inhibits its transcription in hepatocytes. Two previous reports also showed that IRF6 regulates Pparγ gene in macrophages and endothelial cells . These studies, combined with our findings, suggest a more generalized transcriptional target gene for IRF6; however, we investigated a unique function of IRF6 in regulating different disease from the current report with different molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Ardenne and Reitnauer (27) demonstrated that hsa-miR-106a suppressed proliferation and induced apoptosis. Application of miR-106a mimics induced cerebrovascular endothelial cell death under oxygen-glucose deprivation conditions (28). Therefore, DGCR8 promoting hsa-miR-106a transcription might be one of the important reasons for enhancing radiation sensitivity.…”
Section: Discussionmentioning
confidence: 99%